Understanding the Interplay Between Industrial Mining Policy, Innovation, and Firm Business Performance - Jayana, Agus; Bin Habidin, Nurul Fadly; Binti Zainol, Zuraidah; Hidayat, Rizky (Journal of Business and Economics Research (JBE), 2024)
The relationship between industrial mining policy, innovation and firm business performance is the subject of this research paper. The purpose of the study is to explore how innovation can influence business performance and whether Indonesia has a role in changing global markets. The study adopts a cross-sectional design and uses both quantitative research methods as per positivist paradigm, as well qualitative approaches. The collected data is subjected to quantitative analysis using partial least squares structural equation modeling (PLS-SEM). The specific focus of this investigation centers around Indonesian mining firms possessing mining business permits (IUP), with a total sample size of 385 respondents who participated in the survey. The findings indicate all constructs and dimensions are categorized as substantial and have predictive relevance. This study also demonstrates that innovation acts as a mediator between the industrial mining policy and firm business performance, since the path coefficient of the indirect effect of IMP → IN → FBP (0.496) is higher than the direct effect of IMP → FBP (0.323). In sum, this research emphasizes the significance of innovation in enhancing the positive correlation between the industrial mining policy and firm business performance within the Indonesian mining sector. The lessons of this research have practical applications for policymakers and industry stakeholders. Not only do they offer information about how to make money in the Indonesian mining sector, but also findings that help develop viable economic solutions which can be sustained over time. This research can help change the direction of mining toward sustainability and profit, by making clearer just how much innovation effects performance. This paper fills gaps in the current literature by providing helpful insights into innovation and business performance among Indonesia's miners.